Mineralogical and structural characterization of alteration zones detected by orbital remote sensing at Shalatein District, SE Desert, Egypt - Ramadan, Talaat M.; Kontny, Agnes (Journal of African earth sciences, 2004)
In the Shalatein district, Eastern Desert of Egypt, Landsat Thematic Mapper (TM) data and fieldwork were combined with mineralogical and geochemical investigations in order to detect and characterize alteration zones within Pan-African rocks. The processing of Landsat TM data using ratioing (bands 5/7, 4/5, 3/1 in red, green, blue) showed two different types of alteration zones (type 1 and 2). Type 1 is close to the ophiolitic ultramafic rocks at Wadi Hodein and Wadi Beida areas, whereby type 2 is located within island-arc related metavolcanic rocks at Wadi Beida and Gabal El Qurun areas. Both of these alteration types are concordant with the main NW-SE structural trend. Mineralogical studies indicate that the type 1 alteration consists mainly of calcite, ankerite, magnesite, dolomite and quartz. Chromian spinel, pyrite, and Ni-bearing sulphides (gersdorffite, pentlandite and polydymite) are the main ore minerals within this type. Type 2 alteration is strongly potassium-enriched and pyrophyllite, kaolinite, illite, gypsum and quartz occur. The brecciated quartz-veins, which are associated with these alteration zones, consist of quartz, Fe-hydroxides, hematite and native gold. The gold content reaches up to 5g/t in the alteration zone, while it extends up to 50g/t in the quartz veins. This study presents a mineralogical characterization of such alteration zones and demonstrates the utility of orbital remote sensing for finding unknown alteration zones in the Eastern Desert of Egypt and other arid areas with similar host rock lithologies.
Gesehen am 28.09.2020